New N- and O-arylpiperazinylalkyl pyrimidines and 2-methylquinazolines derivatives as 5-HT7 and 5-HT1A receptor ligands: Synthesis, structure-activity relationships, and molecular modeling studies. Issue 3 (1st February 2017) - Intagliata, Sebastiano; Modica, Maria N.; Pittalà, Valeria; Salerno, Loredana; Siracusa, Maria A.; Cagnotto, Alfredo; Salmona, Mario; Kurczab, Rafał; Romeo, Giuseppe
Graphical abstract: Abstract: Based on our earlier studies of structure activity relationships on 4-substituted piperazine derivatives, in this work we synthesized a novel set of long-chain arylpiperazines with the purpose of elucidating if some structural modifications in the terminal fragment could affect the binding affinity for the 5-HT7 and 5-HT1A receptors. In this new series, the quinazolinone system of the previous derivatives was replaced by a 6-phenylpyrimidine or a 2-methylquinazoline, which were used as versatile building blocks for the preparation of new compounds. A 4-arylpiperazine moiety through a five methylene chain was anchored at the nitrogen or oxygen atom of the heterocyclic scaffolds. The substituents borne by the piperazine nucleus were phenyl, phenylmethyl, 3- or 4-chlorophenyl, and 2-ethoxyphenyl. Binding tests, performed on human cloned 5-HT7 and 5-HT1A receptors, showed that, among the newly synthesized derivatives, 4-[5-[4-(2-ethoxyphenyl)-1-piperazinyl]pentoxy]-6-phenyl-pyrimidine (13 ) and 3-[5-[4-(2-ethoxyphenyl)-1-piperazinyl]pentyl]-2-methyl-4(3 H )-quinazolinone (20 ) displayed the best affinity values, K i = 23.5 and 8.42 nM for 5-HT7 and 6.96 and 2.99 nM for 5-HT1A receptors, respectively. Moreover, the functional properties for both compounds were further evaluated using the cAMP assay. Finally, a molecular modeling study has been performed for 5-HT7 and 5-HT1A receptor homology models to investigate the binding mode of N - and O -alkylated pyrimidinones/pyrimidines4 –13, 2-methylquinazolinones/quinazolines17 –22, and previously reported 2- and 3-substituted quinazolinones23 –30 .